2021
DOI: 10.3389/fneur.2021.646029
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Migraine-Like Headache With Visual Aura Initiated by Endovascular Coiling Treatment for a Posterior Cerebral Artery Aneurysm

Abstract: Cervical, anterior, and middle cerebral artery aneurysm is a causative factor for migraine, and endovascular treatment usually improves migraine headache. Posterior cerebral artery (PCA) aneurysm is a rare condition, and its association with migraine is very rarely reported. In addition, endovascular coiling treatment causing migraine-like headache has never been reported. Here, we describe a newly developed migraine-like headache with visual aura after endovascular coiling treatment for PCA aneurysm in a 31-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Nowadays, it has been found that the high prevalence of RLS was correlated with the commodity of migraine in PWEs, which could be an underlying cause of migraine in PWEs 11 . Epilepsy is often comorbid with migraine, and they share similar symptom profiles, treatment options, and common pathogenic mechanisms, such as hypoxia, CSD, and microthrombi 12,13 . Factors that acutely increasing oxidative stress in the brain, such as high altitude and psychosocial stress, can threaten neuronal viability, which is an immediate precipitant of both seizures and migraine attacks 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, it has been found that the high prevalence of RLS was correlated with the commodity of migraine in PWEs, which could be an underlying cause of migraine in PWEs 11 . Epilepsy is often comorbid with migraine, and they share similar symptom profiles, treatment options, and common pathogenic mechanisms, such as hypoxia, CSD, and microthrombi 12,13 . Factors that acutely increasing oxidative stress in the brain, such as high altitude and psychosocial stress, can threaten neuronal viability, which is an immediate precipitant of both seizures and migraine attacks 14 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Epilepsy is often comorbid with migraine, and they share similar symptom profiles, treatment options, and common pathogenic mechanisms, such as hypoxia, CSD, and microthrombi. 12,13 Factors that acutely increasing oxidative stress in the brain, such as high altitude and psychosocial stress, can threaten neuronal viability, which is an immediate precipitant of both seizures and migraine attacks. 14 PWEs concomitant with migraine also have higher incidence of drug resistance and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy and migraine are the two most common neurological chronic diseases with episodic manifestations (NCDEMs), which are collectively characterized by recurrent episodes of neurological dysfunction that return to baseline between episodes 1 . Epilepsy and migraine, each occupying 20% of outpatient neurological visits, have similar symptom profiles, comorbidities, and treatment options, as well as common pathogenic mechanisms such as hypoxia, cortical spreading depression (CSD), and microemboli 2,3 . In addition, hypoxia can independently trigger ictaform activity, aura, photophobia, and phonophobia, which are common clinical symptoms of NCDEMs 4 …”
Section: Introductionmentioning
confidence: 99%
“…1 Epilepsy and migraine, each occupying 20% of outpatient neurological visits, have similar symptom profiles, comorbidities, and treatment options, as well as common pathogenic mechanisms such as hypoxia, cortical spreading depression (CSD), and microemboli. 2,3 In addition, hypoxia can independently trigger ictaform activity, aura, photophobia, and phonophobia, which are common clinical symptoms of NCDEMs. 4 Patent foramen ovale (PFO), resulted from failed primum and secundum septal fusion during the postnatal period, is one of the most common congenital cardiac malformations, with a prevalence of approximately 20% in the general population, as determined through autopsy studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation